2008
DOI: 10.1186/cc6549
|View full text |Cite
|
Sign up to set email alerts
|

Predicting success in weaning from mechanical ventilation

Abstract: IntroductionIn order to find out the frequency rates of domestic and wild animal bites as well as the evaluation of the prevalence rates of rabies disease in the human population in the Province of Kerman, a retrospective study was designed to analyze statistically the collected recorded data related to this project. Methods This study was conducted within the framework of MPVM student research projects by means of collaboration between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…However, the multivariate analysis in this study suggested that only BNP in the clinical indicators was associated with an increased risk of weaning failure. It is reasonable to assume that the detection of BNP is more stable compared with RSBI and duration of mechanical ventilation, which are easily affected in the clinical setting [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the multivariate analysis in this study suggested that only BNP in the clinical indicators was associated with an increased risk of weaning failure. It is reasonable to assume that the detection of BNP is more stable compared with RSBI and duration of mechanical ventilation, which are easily affected in the clinical setting [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%